India and Pakistan's evolving relationships with the Gulf. Issue 7 (8th August 2016) - Unknown
Abstract : The relationships of South Asian rivals India and Pakistan with Gulf countries are evolving and strengthening. India's focus has shifted towards security and defence cooperation, though it does not seek a dominant or partisan role. Pakistan will continue to try to balance its relations with Gulf Arab states and those with Iran, while its most important bilateral relationship will continue to be with Saudi Arabia.